Pendidikan Karakter Berbasis Al-Qur’an Dalam Pencegahan Terorisme Dan Radikalisme (The Quran-Based Character Education) - Nur Ali (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2020)
Quran and Hadith are the main references of Islamic law. As the sources of Islamic law, the Quran contains a lot of Shari’a, teachings and exhortations for Muslims, including hints of character education. Character education has its own importance in our social system, which significantly impacts on the success of development. Thus, the Quran-based character education needs to be explored and developed in order to provide a broader contribution to national development, particularly in the field of religion.